Factor Structure of the 10-Item Perceived Stress Scale and Measurement Invariance Across Genders Among Chinese Adolescents - Liu, Xiqin; Zhao, Yajun; Li, Jingguang; Dai, Jing; Wang, Xiuli; Wang, Song (Frontiers in Psychology, 2020)
Background: Chinese adolescents encounter a lot of stressors, such as academic burden and parental pressure. However, little is known about their perception of stress. The 10-item Perceived Stress Scale (PSS-10) is a widely used instrument to measure individuals’ appraisal of global stress in academic research and clinical practice. The current study aimed to evaluate the best-fit factor structure model of the PSS-10 and the measurement invariance across gender in Chinese adolescents. Methods: 1,574 Chinese senior high school students completed the PSS-10 (mean age = 15.26 ± 0.56, female = 54%). Confirmatory factor analysis (CFA) was conducted to determine the factor structure of the PSS-10. Multi-group CFA was carried out to test the measurement invariance of the PSS-10 across genders. A subsample (N = 1,060) answered additional questionnaires measuring stressful life events, anxiety and depression to examine the convergent and concurrent validity of the PSS-10. Results: The two-factor model was supported (i.e., χ2 (34) = 332.224, p < 0.001; NNFI = 0.901, CFI = 0.925, RMSEA = 0.075, SRMR = 0.051). Importantly, the model exhibited strong measurement invariance across female and male groups. Furthermore, the PSS-10 had adequate convergent validity for stressful life events (number: r = 0.13, p < 0.001; impact: r = 0.23, p < 0.001) and could explain incremental variance in predicting anxiety (ΔR2 = 0.13, β = 0.38, p < 0.001) and depression (ΔR2 = 0.16, β = 0.41, p < 0.001), suggesting excellent concurrent validity. Conclusions: A two-factor model best fits the structure of PSS-10 among Chinese adolescents, with strong measurement invariance between gender groups, demonstrating its validity for assessing perceived stress among Chinese adolescents.